Perpetuating Commodification of Suffering: How Social Determinants of Health Framing Prolongs Historical Racial Inequities - Garssandra Presumey-Leblanc; Megan Sandel (Mary Ann Liebert, 2022)
Background: In the United States, social determinants of health (SDOH) and the marginalization of Black and Indigenous people of color (BIPOC) populations often result in negative health outcomes, but may miss the underlying historical causes for these disparities. While the health and human services (HHS) workforce is trained to recognize and address negative SDOH, it is unclear how historical trauma impacts this contemporary work. Materials and Methods: As part of a broader ethnographic study, 2 MLP affiliates and 6 BIPOC women HHS workforce members who had taken SDOH trainings were interviewed using semi-structured interviews. Themes were explored around the language of SDOH and how the medical and legal system responses to SDOH results in negative health outcomes and historical trauma. Results: Themes emerged around American medical and legal institutions, meant to care for patients, have been wearied by the power struggle between politics, budgets, and the value of financial profit. Under such competing loads, workforce members feel trapped in financially-based hierarchies and established risk-designations. This current conceptualization of the language and coding of SDOH has created a globalization or commodification of suffering that mirrors historical hierachies in slavery. Conclusions: The variable naming of SDOH draws attention away from the root causes of inequities and the individualization of the social risks creates a cycle of commodification of suffering, instead of addressing the historical and structural antecedents. Future work should explore how to adapt to these intersections.